2018
DOI: 10.1016/j.celrep.2018.07.030
|View full text |Cite
|
Sign up to set email alerts
|

Coding of Self and Other’s Future Choices in Dorsal Premotor Cortex during Social Interaction

Abstract: Representing others' intentions is central to primate social life. We explored the role of dorsal premotor cortex (PMd) in discriminating between self and others' behavior while two male rhesus monkeys performed a non-match-to-goal task in a monkey-human paradigm. During each trial, two of four potential targets were randomly presented on the right and left parts of a screen, and the monkey or the human was required to choose the one that did not match the previously chosen target. Each agent had to monitor th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Figure 1 illustrates the spatial NMTG (S-NMTG) and object NMTG (O-NMTG) tasks described in a previous work (Cirillo et al., 2018) and in more details in Methods.
Figure 1Behavioral TaskTemporal sequence of events of one example trial of the object non-match-to-goal task (O-NMTG). Left panel shows the peripheral targets used during the spatial and object versions of the task.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 illustrates the spatial NMTG (S-NMTG) and object NMTG (O-NMTG) tasks described in a previous work (Cirillo et al., 2018) and in more details in Methods.
Figure 1Behavioral TaskTemporal sequence of events of one example trial of the object non-match-to-goal task (O-NMTG). Left panel shows the peripheral targets used during the spatial and object versions of the task.
…”
Section: Resultsmentioning
confidence: 99%
“…The database for this study consisted of 328 neurons (210 and 118 from monkey 1 and monkey 2, respectively) that were selected by using the single-unit stability method described in Cirillo et al. (2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NMTG task is considered to be a task with a high cognitive demand, because the monkeys are required to apply a counterintuitive rule 47,[50][51][52][53][54] and continuously monitor the trials performed, because the correct choice in one trial depends on the previous trial. We showed that this task could be learned using a home-cage training approach.…”
Section: Discussionmentioning
confidence: 99%
“…New recording techniques allow for the simultaneous recording of much larger numbers of neurons, in some cases up to hundreds of neurons and across several brain regions (Dotson, Hoffman, Goodell, & Gray, 2017;Nicolelis et al, 2003). The PSTH-based method has been shown to be very sensitive to the number of neurons used, with an increase in accuracy with an increase in the number of neurons considered (Cirillo, Ferrucci, Marcos, Ferraina, & Genovesio, 2018;Falcone, Cirillo, Ferraina, & Genovesio, 2017;Genovesio, Brasted, et al, 2006;Lebedev, Messinger, Kralik, & Wise, 2004;Marcos & Genovesio, 2016;Marcos, Nougaret, Tsujimoto, & Genovesio, 2018;Marcos, Tsujimoto, & Genovesio, 2017). Thus, at least two open questions arise from these new kinds of data sets: (1) Would the two methods reach similar levels of performance for large numbers of neurons, or, even in those cases, would the HMMs always be capable of extracting further information than that obtain from the mean response?…”
Section: Discussionmentioning
confidence: 99%